2018
DOI: 10.1002/ajmg.a.40628
|View full text |Cite
|
Sign up to set email alerts
|

Novel variants in SPTAN1 without epilepsy: An expansion of the phenotype

Abstract: We describe two unrelated children with de novo variants in the non-erythrocytic alpha-IIspectrin (SPTAN1) gene who have hypoplastic brain structures, intellectual disability, and both fine and gross motor impairments. Using agnostic exome sequencing, we identified a nonsense variant creating a premature stop codon in exon 21 of SPTAN1, and in a second patient we identified an intronic substitution in SPTAN1 prior to exon 50 creating a new donor acceptor site.Neither of these variants has been described previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
0
16
0
2
Order By: Relevance
“…As the last two spectrin repeats are required for heterodimer formation, mutations in this C-terminal region of SPTAN1 are critical and might have major consequences. In addition, Gartner et al [107] suggested that deleterious variants of SPTAN1 may cause reduced mRNA expression as observed in two unique SPTAN1 variants.…”
Section: Sptan1 In Cancer Development and Progressionmentioning
confidence: 99%
“…As the last two spectrin repeats are required for heterodimer formation, mutations in this C-terminal region of SPTAN1 are critical and might have major consequences. In addition, Gartner et al [107] suggested that deleterious variants of SPTAN1 may cause reduced mRNA expression as observed in two unique SPTAN1 variants.…”
Section: Sptan1 In Cancer Development and Progressionmentioning
confidence: 99%
“…Our patient's neuropathy and neuropsychological profile provide an interesting link between axonal neuropathy phenotypes described by Beijer et al, and previously described non-epileptic neurodevelopmental phenotypes. Gartner et al reported two patients, aged 12 and 7, with de novo nonsense or splice mutations that decreased the level of alpha-II spectrin (Gartner et al, 2018) consistent with a haploinsufficiency mechanism. These patients resembled our patient by having developmental disorder and impairment of motor performance from early age.…”
Section: Sirmentioning
confidence: 97%
“…Before this, alterations of SPTAN1 have been linked to early-infantile epileptic encephalopathy or neurodevelopmental phenotypes often with epilepsy (Syrbe et al, 2017;Gartner et al, 2018) . De novo in-frame deletions/duplications, missense, truncating and splice mutations have been described behind these phenotypes.…”
Section: Sirmentioning
confidence: 99%
See 1 more Smart Citation
“…Human mutations in αII spectrin (SPTAN1) link to early infantile epileptic encephalopathy (EIEE) type 5 (West Syndrome), characterized by refractory seizures, intellectual disability, agenesis of the corpus callosum and hypomyelination [38][39][40][41]. Other SPTAN1 neurological disorders include juvenile onset hereditary motor neuropathy and hereditary spastic paraplegia [28,[42][43][44][45][46].…”
Section: Spectrinopathiesmentioning
confidence: 99%